The Technology Acceptance Model of Online Game in Indonesian Adolescents - Jap, Tjibeng (UI Scholars Hub, 2017)
Online games have become a mainstream source of entertainment in the world, including Indonesia. The present study uses an adaptation of the Technology Acceptance Model (TAM) to help us understand how online game is accepted in Indonesia. The participants were school students (N = 1 498) from Year 7 to Year 12 recruited from several schools in Surabaya, East Java, Indonesia. A modified version of the original measures of the TAM was used to assess perceived ease of use and usefulness of online game. Confirmatory factor analysis was used to investigate the construct validity of each measure and path analysis with structural equation modeling was used to test the hypotheses. The results confirmed the relevance of previous established constructs, perceived ease of use, perceived usefulness, and intention in an online game setting in Indonesia, as well as the hypothesized relationships among these constructs according to TAM. Furthermore, the good model fit suggests that TAM is a valid and relevant research model to understand online game usage among Indonesian school students. Although further studies are necessary, the results support the notion that online games in the setting of Indonesian school students is just like any other technology in adult and business settings.